Assessment of the Level of Software Development Using CMMI-Dev 1.3 on the Unjani Official Web - Ghaniiy, Gheral Naza; Chrisnanto, Yulison Herry; Abdillah, Gunawan (Bincang Sains dan Teknologi, 2025)
UNJANI website ranked 186 in Webometric ranking. Webometric is a ranking system of universities around the world conducted by Cybermetrics Labs which is useful to determine the ranking in terms of the level of performance indicators of universities, which include Visibility, Openness, Excellence. The purpose of this study was to assess the level of maturity of the software development process on the UNJANI website using CMMI Dev 1.3. This study uses quantitative methods, with a survey approach to the person in charge and manager of the UNJANI website. Quantitative research is a way to obtain research data measured using tools such as surveys, questionnaires, or experiments, and analysed with statistical methods to find certain patterns, relationships, or trends. The results of this study found that out of 7 CMMI Dev.1.3 process areas, some areas are in accordance with the standard process of making the UNJANI website and some process areas are not in accordance with the CMMI Dev 1.3 framework. The maturity level of the UNJANI website is in the category of partially implemented in most process areas, with the highest GAP (50%) in Configuration Management (CM) and the lowest GAP (30%) in Project Monitoring and Control (PMC). The conclusion of this research reveals that UNJANI website still needs improvement in configuration management, change recording, and feature quality evaluation before release.